2021
DOI: 10.1021/acsmacrolett.0c00903
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alicyclic Conformation-Isomerization in the Photomechanical Performance of Azobenzene-Functionalized Cross-Linked Polyimides Containing Tetra-Substituted Cyclohexane Moieties

Abstract: The classical "chair-twist boat−boat" conformational dynamics (CD) of cyclohexane is thermally activated. Here we report on the photoinduced/azobenzene-assisted CD of bilaterally fused cyclohexane moieties contributing to large photomechanical response of cross-linked azobenzene-functionalized polyimides (X-azoPI), based on 1,2,4,5-cyclohexane-tetracarboxylic-dianhydride (CHDA), exhibiting a photobending angle and photogenerated stress, up to ∼90°and 370 kPa, respectively. In contrast, X-azoPI containing plana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Our previous extensive experience with bicyclo[2.2.2]octene skeletons [ 28 , 29 , 30 ] has shown that they can provide a very robust and chemically inert nonpeptide skeleton appropriate for further derivatizations. Bicyclo[2.2.2]octenes with fused succinic anhydride rings (i.e., ethenopyrrolo[3,4- f ]isoindoles) can be thus used as starting compounds for transformations with variously substituted primary amines or hydrazine and its derivatives (having one NH 2 group unsubstituted); additionally, they are nowadays quite common fragments of various polymeric materials [ 31 ] and zeolites [ 32 , 33 , 34 , 35 ]. In the final step of the molecular design, we combined the pharmacophoric requirements of the H1–H4 units with the proposed rigid bicyclo[2.2.2]octene scaffold fused to two succinimide rings to form a model compound 11a , which we were also able to synthesize.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous extensive experience with bicyclo[2.2.2]octene skeletons [ 28 , 29 , 30 ] has shown that they can provide a very robust and chemically inert nonpeptide skeleton appropriate for further derivatizations. Bicyclo[2.2.2]octenes with fused succinic anhydride rings (i.e., ethenopyrrolo[3,4- f ]isoindoles) can be thus used as starting compounds for transformations with variously substituted primary amines or hydrazine and its derivatives (having one NH 2 group unsubstituted); additionally, they are nowadays quite common fragments of various polymeric materials [ 31 ] and zeolites [ 32 , 33 , 34 , 35 ]. In the final step of the molecular design, we combined the pharmacophoric requirements of the H1–H4 units with the proposed rigid bicyclo[2.2.2]octene scaffold fused to two succinimide rings to form a model compound 11a , which we were also able to synthesize.…”
Section: Resultsmentioning
confidence: 99%
“…The polarized-light-induced deformation of azo-PIs has been widely studied, in which the repeated trans-cis-trans isomerization causes the reorientation of azobenzene perpendicular to the polarization direction (the Weigert effect). [20][21][22][23][24][25][26][27][28] This reorientation process leads to the conformational changes of polymer networks in the polarization direction, thereby resulting in deformation. White et al first synthesized a deformable polyimide with azobenzene as the crosslinker, and it exhibited a bending angle of ∼20°after irradiation with polarized bluegreen light for 30 min.…”
mentioning
confidence: 99%
“…20 Subsequently, some efforts have been made to investigate the influence of the molecular structure on the photomechanical response of azo-PIs. [21][22][23][24][25][26][27] For example, freely rotating structures 24 or bulky substituents 25 increase the segmental mobility as well as free volume, which promotes the ability of azobenzene to undergo efficient reorientation and induce conformational changes, endowing azo-PIs with large deformation. However, as they lack the cooperative effect of azo-LCPs, the deformation of azo-PIs through reorientation is relatively slow, which is unfavourable for light-driven actuators.…”
mentioning
confidence: 99%
“…However, the conventional PI synthesis process requires the use of a solvent and high temperature for thermal imidization, making the replica molding impossible for the construction of 3D microstructured PI. The thermal imidization temperature is ∼300 °C, which is a very high temperature to retain the shape of the general polymeric molds. Furthermore, the dimethylacetamide, commonly used in the processing of PI, cannot be completely removed, owing to its high boiling point of ∼165 °C and is harmful to the human body.…”
mentioning
confidence: 99%